Analisis Penegakan Hukum dan Perlindungan Konsumen terhadap Praktik Penagihan dalam Layanan Pendanaan Bersama Berbasis Teknologi Informasi - Chris Leo Yonatal Gurning; Christin Septina Basani (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
The rapid development of financial technology (fintech), particularly Peer-to-Peer Lending services or Layanan Pendanaan Bersama Berbasis Teknologi Informasi (LPBBTI), has provided easier access to financing for the public. However, it has also raised serious concerns regarding unethical debt collection practices, often involving intimidation and privacy violations. This research aims to analyze the legal framework governing debt collection and consumer protection in fintech, as well as to assess the effectiveness of law enforcement against such violations. The study employs a normative juridical method using the statute and conceptual approach, examining regulations such as Law No. 8 of 1999 on Consumer Protection, Law No. 27 of 2022 on Personal Data Protection, OJK Regulation (POJK) No. 40 of 2024, and the AFPI Code of Conduct. The findings indicate that although the legal framework establishes principles of transparency, fairness, data protection, and a prohibition on intimidating collection practices, its implementation remains far from optimal. The Financial Services Authority (OJK) recorded thousands of complaints related to unethical collection methods, highlighting the gap between normative law and actual practices in the industry. Enforcement through administrative, ethical, and criminal sanctions has not provided sufficient deterrent effect nor ensured remedies for consumers, particularly regarding immaterial losses. Therefore, strategic measures are required, including strengthening supervisory mechanisms, integrating complaint platforms, mandating compensation for consumers as part of administrative sanctions, and enhancing public financial literacy to achieve effective and fair consumer protection in the fintech sector.